Pengaruh Modal Kerja dan Investasi Terhadap Non Performing Financing Pada Bank Pembiayaan Rakyat Syariah Periode 2015-2019 - Miranda, Reza (JYRS: Journal of Youth Research and Studies, 2021)
The growth of Islamic banks has increased from year to year. The indicator for the growth of Islamic banks can be seen from their total assets. The phenomenon in this study is that working capital has increased significantly, then investment from five years has increased while the NPF has fluctuated so that it affects the distribution of working capital and investment financing which causes an imbalance in financing. From the results of the disbursed financing will generate profitability. One of the profitability measurement tools is NPF which shows the ability of bank management in assessing non-performing financing from financing disbursed by Islamic banks. If the NPF decreases, it will have a positive impact on the growth of the total assets of Islamic banks. This research uses associative quantitative research which explains the effect of two or more variables by analyzing data using numerical methods in statistics. Data analysis techniques in this study used descriptive statistics, classical assumption test and hypothesis testing. The results of this study indicate that working capital financing and investment simultaneously there is a significant effect against NPF in Islamic people's financing banks in Indonesia for the 2015-2019 period, with a probability value of 0.000000 < 0.05 (sig. value). As for working capital partiallysignificant effect on NPF in Islamic people's financing banks in Indonesia for the 2015-2019 period, with a probability value of 0.000 < 0.05. While investment too have a partial and significant influence on NPF in Islamic people's financing banks in Indonesia 2015-2019 period, with a probability value of 0.000 < 0.05.